Traceability in food supply chains: SME focused traceability framework for chain-wide quality and safety - Curto, João Paulo (2022)
It is relevant for traceability systems to have a common structure for information exchange. Without it, these systems lose much of their utility as they will only be usable internally and will have reduced capacity to add value to products and manage recalls. Based on extensive literature review, a non-proprietary framework for traceability was developed. This framework encompasses whole food supply chains and aims to maintain records of quality and safety while not necessitating mature IT capabilities, uncommon characteristic of SME’s. As such the volume of information is divided between all stakeholders according to their necessities and funding capacities. Most of the information is stored by regulators as they have access to more funding. This improves the ease and flexibility of implementation of traceability systems by the companies. Tools were developed and simulated, and all results are presented, clearly demonstrating the capability for quality information sharing through food supply chains which in turn can increase transparency between consumers and producers as well as adjusting the quality to the desired end use.